In vitro and in vivo testing of nanofibrous membranes doped with alaptide and L-arginine for wound treatment - Mikeš, Petr; Brož, Antonín; Sinica, Alla; Asatiani, Nikifor; Bačáková, Lucie (Biomedical materials, 2020)
We have prepared a candidate biocompatible construct for skin wound healing based on electrospun polycaprolactone (PCL) nanofibrous membranes. The membrane material was loaded either with L-arginine or with alaptide, or with a mixture of both bioactive components. Alaptide is a spirocyclic synthetic dipeptide, an analogue of melanocyte-stimulating hormone release-inhibiting factor. L-arginine is an amino acid with a basic guanidine side chain. It is a direct precursor of nitric oxide, which plays a pivotal role in skin repair. The presence and the distribution of the additives were proved with high-performance liquid chromatography, Fourier-transform infrared spectroscopy and Raman spectroscopy. The influence of L-arginine and alaptide on the morphology of the membrane was characterized using scanning electron microscopy. No statistically significant correlation between fiber diameter and drug concentration was observed. The membranes were then tested in vitro for their cytotoxicity, using primary human dermal fibroblasts, in order to obtain the optimal concentrations of the additives for in vivo tests in a rat model. The membranes with the highest concentration of L-arginine (10 wt. %) proved to be cytotoxic. The membranes with alaptide in concentrations from 0.1 to 2.5 wt.%, and with the other L-arginine concentrations (1 and 5 wt.%), did not show high toxicity. In addition, there was no observed improvement in cell proliferation on the membranes. The in vivo experiments revealed that membranes with 1.5 wt.% of alaptide or with 1.5 wt.% of alaptide in combination with 5 wt.% of L-arginine markedly accelerated the healing of skin incisions, and particularly the healing of skin burns, i.e. wounds of relatively large extent. These results indicate that our newly-developed nanofibrous membranes are promising for treating wounds with large damaged areas, where a supporting material is needed.
Keywords: Tissue Engineering; Spectroscopy, Fourier Transform Infrared; fibroblasty; Electrodes; Rats, Wistar; testování materiálů; Cell Proliferation; Fibroblasts; fluorescenční mikroskopie; neuropeptidy; vysokoúčinná kapalinová chromatografie; Materials Testing; Spectrum Analysis, Raman; Ramanova spektroskopie; techniky in vitro; Electrochemistry; potkani Wistar; kůže; Arginine; Chromatography, High Pressure Liquid; elektrody; tkáňové inženýrství; krysa rodu Rattus; Drug Delivery Systems; Animals; lidé; biokompatibilní materiály; elektrochemie; ženské pohlaví; nanovlákna; Microscopy, Fluorescence; Peptides, Cyclic; Humans; Skin; zvířata; In Vitro Techniques; Wound Healing; Rats; Tissue Scaffolds; Nanofibers; Peptides; arginin; proliferace buněk; peptidy; tkáňové podpůrné struktury; cyklické peptidy; Female; Biocompatible Materials; lékové transportní systémy; Neuropeptides; spektroskopie infračervená s Fourierovou transformací; hojení ran